Fully-Woven Textile Implementation of a Circularly Polarized Rectenna for Wireless Power Transfer Applications - Miguel Fernandez; Carlos Vazquez; Samuel Ver Hoeye (IEEE Access)
This work describes a fully-woven textile rectenna for Wireless Power Transfer applications in the 2.4 GHz frequency band. The radiating element is based on a square patch fed through an offset T-match network to which the rectifier is connected. This feeding structure provides impedance matching with the rectifier without requiring additional networks, which results in a compact layout. On the other hand, its particular location at one or the patch corners is exploited to generate circular polarization. The rectifier is based on a single Schottky diode to provide a layout suitable for textile integration. It is mounted on a carrier thread which is then woven together with the rest of the textile structure of the antenna, providing a large degree of integration and robustness. The measured RF-DC conversion efficiency is about 50% for -10 dBm available power at the rectifier input, which is comparable to state-of-the-art values reported for rectennas implemented in conventional rigid substrates, demonstrating the viability of woven technology in the microwave frequency band. Furthermore, the frequency weighted and the power frequency weighted conversion efficiency figures of merit were evaluated, showing a considerably improvement with respect to previously reported works.